Latvijas Bankas un Valsts Cilvēktiesību biroja problemātika Latvijas Republikas valsts pārvaldē - Bobrovskis, Andris (Latvijas Universitāte, 2007)
State administration in Latvia is vested to the Cabinet of Ministers. The voters control it by means of the Parliament (i.d. Saeima). Some of the independent institutions perform their functions better in order which is not stated in the Constitution. Amendments are necessary to solve this problem. A working group was founded for elaboration of bill for Constitution amendments. The group is working on specific versions of amendments. The author examines and analyses “short” and “long” amendment versions in many sections of this work. In this work the author examines the appearance, development and necessity of independence in actions of state administration institutions as well the necessity to state them in the Constitution. Taking into account that the thesis work is limited, author consider specifically only two institutions – Bank of Latvia and The Human rights bureau. Author comes to a conclusion that these institutions should be conferred a status of independent state administration institutions in the Constitution so as it was done in many European countries.
Latvian Bank and State Human Berau problems in the state administration of Latvia
Keywords: Tiesības